(untitled) (American Journal of Pedagogical and Educational Research, 2024)
It is natural for educators to form pre-school children from an early age, to educate them into independent-minded, socially flexible young people. In order to fulfill these tasks and be able to fulfill them fully, each educator must have high knowledge, pedagogical technique and moral virtue in his field. It is an urgent task and the need of the hour to train future teachers in the process of social adaptation of students in a preschool educational organization. A distinctive feature of the child’s socialization is that it is difficult for him to evaluate and control the norms of behavior promoted by society.